2015
DOI: 10.4314/ahs.v15i1.28
|View full text |Cite
|
Sign up to set email alerts
|

Women’s status within the household as a determinant of maternal health care use in Nigeria

Abstract: Background: Although gender inequality is often cited as a barrier to improving maternal health in sub-saharan Africa, there is lack of empirical data on how women's socio-cultural characteristics may influence use of health services in Nigeria. Objective: To describe how women's position in the household affects receipt of maternity care services. Methods: Secondary data analysis of 10,052 and 4,590 currently married women aged 15 to 49 years from the 2008 Nigerian DHS who receive skilled antenatal and delive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
64
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(89 citation statements)
references
References 15 publications
20
64
0
5
Order By: Relevance
“…This study found significant relationships between women autonomy, antenatal care visits and health facility delivery. The findings of this study are consistent with the findings of (Asweto et al, 2014;Baral et al, 2010;Bhandari et al, 2017;Deo et al, 2015;Fawole and Adeoye, 2015;Woldemicael, 2007b), who found that maternal healthcare utilisation is influenced by women autonomy. Also, the findings of this study are in agreement with the findings of Sharma et al, (2007) where it was stated that women with greater autonomy irrespective of physical and financial resources are able to manage their own children's health care and make fertility decisions too.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This study found significant relationships between women autonomy, antenatal care visits and health facility delivery. The findings of this study are consistent with the findings of (Asweto et al, 2014;Baral et al, 2010;Bhandari et al, 2017;Deo et al, 2015;Fawole and Adeoye, 2015;Woldemicael, 2007b), who found that maternal healthcare utilisation is influenced by women autonomy. Also, the findings of this study are in agreement with the findings of Sharma et al, (2007) where it was stated that women with greater autonomy irrespective of physical and financial resources are able to manage their own children's health care and make fertility decisions too.…”
Section: Discussionsupporting
confidence: 93%
“…Studies have examined the relationship between women's autonomy and utilisation of any or all of the maternal health care services, and have found association between them (Asweto et al, 2014;Baral et al, 2010;Bhandari et al, 2017;Hagos et al, 2014;Lowe et al, 2016;Speizer et al, 2014;Thapa, 2012;Tiruneh et al, 2017). Other factors such as age, education, employment or labour force participation and wealth quintile have also been found to be associated with maternal healthcare utilisation (Acharya et al, 2017;Adhikari, 2016;Asweto et al, 2014;Banke-Thomas et al, 2017;Baral et al, 2010;Dahiru and Oche, 2015;Deo et al, 2015;Fawole and Adeoye, 2015;Kamiya, 2010;Okeshola and Sadiq, 2013;Sebayang et al, 2017;Sharma et al, 2007;Situ, 2013;Tarekegn et al, 2014;Teklehaymanot et al, 2017;Tiruneh et al, 2017;Urbaeva, 2015;Woldemicael, 2007aWoldemicael, , 2007bWorkineh and Hailu, 2014;Yaya et al, 2017). Umar (2017) submitted that the ability of a young woman to make independent decisions and take appropriate actions on her reproductive desire is dependent on her level of autonomy especially in a society like Nigeria where in some cultures young girls Awoleye et al 63 are married off to older men.…”
Section: Introductionmentioning
confidence: 99%
“…Household size is measured as the number of persons in a particular household that are dependent on the pregnant mother for their daily sustenance [7, 38]. It is widely acknowledged that women with large family sizes tend to underutilise maternal healthcare services due to excessive demand of their money, time, and other resources [18].…”
Section: Related Literaturementioning
confidence: 99%
“…6,14,15 Certain sociodemographic factors such as sex, educational and socioeconomic status are known to influence the awareness about available health-care services and thus, could either promote or serve as a barrier to the uptake of available health-care services. [16][17][18][19] These factors could differently affect the uptake of such services among people of differing sociodemographic factors in the same setting. Irrespective of these factors, a prepayment scheme as is available under the NHIS could to a large extent ameliorate observed differences in the uptake of health-care services, and therefore be used as a platform for equitable access to available healthcare services regardless of sociodemographic divides.…”
Section: Introductionmentioning
confidence: 99%